1995
DOI: 10.1007/bf02220440
|View full text |Cite
|
Sign up to set email alerts
|

Papillary dilation vs sphincterotomy in endoscopic removal of bile duct stones a randomized trial with manometric function

Abstract: To circumvent the long-term effects of papillary ablation for extracting common bile duct stones (< 12 mm in diameter) in endoscopic sphincterotomy (EST), endoscopic papillary dilation (EPD) was attempted in 20 patients. To evaluate papillary function before and after the procedures, manometry of the sphincter of Oddi was carried out in 13 with EPD and 10 of 20 patients with EST. Extraction of all stones was successful (100%) in both groups at an equal rate. Repeated numbers of procedures were common in both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(109 citation statements)
references
References 30 publications
5
101
0
Order By: Relevance
“…3 5 6 The most important potential advantage (as compared with sphincterotomy) was thought to be the ability of the sphincter to recover within a few weeks of dilatation. 4 This might then prevent some of the long term risks referred to. Recently, during the preparation of this manuscript, a study comparing the long term manometric effects of ES versus EBD on the SO was published 19 showing only partial recovery of the sphincter but a lower incidence of recurrent CBD stones, cholangitis, and pancreatitis in the EBD group was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 5 6 The most important potential advantage (as compared with sphincterotomy) was thought to be the ability of the sphincter to recover within a few weeks of dilatation. 4 This might then prevent some of the long term risks referred to. Recently, during the preparation of this manuscript, a study comparing the long term manometric effects of ES versus EBD on the SO was published 19 showing only partial recovery of the sphincter but a lower incidence of recurrent CBD stones, cholangitis, and pancreatitis in the EBD group was found.…”
Section: Discussionmentioning
confidence: 99%
“…2 Fears of an increased incidence of ascending cholangitis and de novo formation of bile duct stones post ES, especially in younger patients, have led to the revival of endoscopic balloon dilatation (EBD) of the SO. 3 This technique which results in temporary destruction 4 of the sphincter was first used in the 1980s and was abandoned amid fears of unacceptably high risks of acute pancreatitis. 5 6 MacMathuna et al in a study of 100 patients who underwent EBD found a 5% incidence of post procedural pancreatitis, a value very similar to the pancreatitis risk after ES.…”
mentioning
confidence: 99%
“…Additionally, they also suggested that the sphincters might be divided into three topographical groups, as extramucosal, intramucosal, and submucosal sphincters. Topographical classification was proven to be useful in endoscopic sphincterotomy and in endoscopic papillar balloon dilatation operations in clinical researches (3,9,10). Moreover, it was noted that endoscopic operations were considered as being easier at the submucosal region, whereas the operations on the sphincters at any other area would cause complications (3,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The holy grail of evidence-based medicine, randomized controlled trials (RCT), has shown PBD to be almost as effective as sphincterotomy for stone removal, thereby establishing it as a standard procedure. 4,5 However, subsequent RCT have concluded that endoscopic sphincterotomy should remain the standard procedure for removing common bile duct (CBD) stones [6][7][8][9] ( Table 1). Eventually, a meta-analysis confirmed PBD to be as effective as sphincterotomy, 10 but a Cochrane systematic review found it to be slightly less effective than sphincterotomy.…”
Section: Refining Papillary Balloon Dilation: Less Is Better!mentioning
confidence: 99%